Can the Y balance test identify those at risk of contact or non-contact lower extremity injury in adolescent and collegiate Gaelic games?. Issue 10 (October 2020) - O'Connor, Siobhán; McCaffrey, Noel; Whyte, Enda F.; Fop, Michael; Murphy, Brendan; Moran, Kieran
Abstract: Objectives: Lower extremity (LE) injuries are common in Gaelic games and lead to a significant economic and injury burden. Balance is considered a predictor of injury in other sports, however no research has examined its effect on LE injury in Gaelic games. This study aims to present normative data for the Y Balance Test (YBT), determine whether the YBT can identify those at risk of contact and non-contact LE and ankle injuries and generate population specific cut-off points in adolescent and collegiate Gaelic games. Design: Prospective cohort study. Methods: A convenience sample of 636 male adolescent (n = 293, age = 15.7 ± 0.7 years) and collegiate (n = 343, age = 19.3 ± 1.9 years) Gaelic footballers and hurlers were recruited. The YBT was completed and injuries were assessed at least weekly over one season. Univariate and logistic regression was performed to examine if the YBT can classify those at risk of LE-combined and ankle injuries. ROC curves were used to identify cut-off points. Results: Gaelic players performed poorly in the YBT and between 31-57% of all players were identified as at risk of injury at pre-season using previously published YBT cut-off points. However, poor YBT scores were unable to ascertain those at risk of contact or non-contact LE-combined and ankle injuries with sufficient sensitivity. High specificity was noted for contact LE-combined and non-contact ankle injuries. Conclusions: The YBT as a sole screening method to classify those at risk of LE and ankle injuries in Gaelic games is questionable. However, the YBT may be a useful preliminary screening tool to identify those not at risk of contact LE-combined or non-contact ankle injury. Generalising published cut-off points from other sports is not supported.